Nilai Prognostik Hiperglikemia terhadap Kejadian Gagal Jantung pada Penderita Sindroma Koroner Akut - Jamaluddin Jamaluddin; Zaenab Djafar (Halu Oleo University, 2018)
Hyperglycemia is a important prognostic factor in acute coronary syndrome patients. Recent decades data shows significant relationship between admission hyperglycemia and heart failure that increase among acute coronary syndrome(ACS) patients. Aim of study is to assess relationship between hyperglycemia and heart failure among ACS patients. This is a prospective cohort study, which was held on March to April 2014 among 83 ACS patients in CVCU Wahodin Sudorohusodo Hospital. Patients was grouped into two groups, hyperglycemic ACS group and normoglycemic one. Heart failure events at each group was observed within first 30 days after infarction. In this study, it found heart failure event were higher in hyperglycemic group than in normoglycemic group (30 vs 8, RR 2.7, p = 0.04). Conclusion of this study was hyperglycemia is related to heart failure event among ACS patients.Keyword: acute coronary syndrome, hyperglycemia, heart falure